Managing Innovation in the Specialty Coffee Industry. Case Study: Asociación de Cultivadores de Apía, Risaralda–Asoapia - Alzate Hoyos, César Andrés (Sociedad y Economía, 2013)
This paper builds upon the discussion of the concept of innovation associated with environmentalissues. The innovative capacity of the organization –ASOAPIA– is evaluatedby defining criteria to analyze the impact of the social appropriation of environmentalknowledge. The importance of this approach resides in the possibility offered by thecomprehension and understanding of a territory and the ability to propose a relaunchingof the creative capacity of the cooperatives.